2018
DOI: 10.3389/fpsyt.2018.00613
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Persistent Medically Unexplained Physical Symptoms: Findings From a General Population Study

Abstract: Objective: To explore the persistency of Medically Unexplained Symptoms (MUS) and its prognostic factors in the general adult population. Knowledge of prognostic factors of MUS may indicate possible avenues for intervention development.Methods: Data were derived from the Netherlands Mental Health Survey and Incidence Study-2 (NEMESIS-2), a nationally representative face-to-face cohort study among the Dutch general population aged 18–64 years. We selected subjects with MUS at baseline and who participated at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…Higher education, higher levels of physical functioning, and higher emotional wellbeing at baseline are associated with low, stable symptom severity. This is in line with previous research that suggests that these factors have a positive influence on overall functioning and wellbeing (van Eck van der Sluijs et al, 2018). Here, we also found that the lower one rates his or her own general health, the lower the odds that one has persisting common somatic symptoms.…”
Section: Predictors Of Stable and Increasing Common Somatic Symptomssupporting
confidence: 93%
“…Higher education, higher levels of physical functioning, and higher emotional wellbeing at baseline are associated with low, stable symptom severity. This is in line with previous research that suggests that these factors have a positive influence on overall functioning and wellbeing (van Eck van der Sluijs et al, 2018). Here, we also found that the lower one rates his or her own general health, the lower the odds that one has persisting common somatic symptoms.…”
Section: Predictors Of Stable and Increasing Common Somatic Symptomssupporting
confidence: 93%
“…Many studies examined the association between SSD and the presence of chronic disease. They revealed a strong association, increasing in strength, with an increasing number of chronic diseases diagnosed in a single person [ 20 , 27 ]. For example, a large population-based study found a strong association between heart attacks and the history of major surgeries and SSD [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Different from the previous construct somatoform disorders, the concept “medically unexplained“ has been removed in SSD; therefore, SSD may co-exist in patients with medical comorbidity. 32 , 33 SSD-12 has been found to effectively diagnose SSD in a population with medical comorbidity. 31 Third, though diagnosing SSD is not the strength of CABAH, its abundant cognitive measurements may still have clinical values.…”
Section: Discussionmentioning
confidence: 99%